Multiprofessional collaboration in recognizing situations of violence in public emergency services: limits to interprofessionality - Sandra Souza da Silva; Luiza Jane Eyre de Souza Vieira; Raimunda Magalhães da Silva; Débora Rodrigues Guerra Probo; Samira Valentim Gama Lira de Alencar (O Mundo da Saúde, 2026)
Interprofessional collaboration constitutes an essential strategy for comprehensive care in urgency and emergency services, especially in recognizing situations of violence, which are frequently veiled and underreported in daily hospital routine. The objective was to analyze the verbalizations of the multiprofessional team regarding collaborative practices in recognizing different situations of violence identified within the context of care at a tertiary public emergency service in Ceará. A qualitative study was conducted in a public tertiary referral hospital for cardiopulmonary care. A total of 34 health professionals selected through the snowball sampling technique participated. Data were generated through semi-structured interviews between May and July 2025 and subjected to thematic content analysis. Participants reported sporadic collaborative efforts, albeit with a predominance of fragmented multiprofessional performance. Communication, reception, and qualified listening were highlighted as central elements to identify situations of violence, even though frequently recognized in an implicit and silenced manner. Work overload, absence of protocols, structural limitations, and insufficient training were identified as the main barriers to the consolidation of interprofessional practices. Findings reveal a gap between the ideal of interprofessionality and the concrete organization of work, contributing to the institutional invisibility of violence in emergency services. The recognition of violence remains supported by individual initiatives and informal workflows. Consolidation of interprofessionality requires reviewing care workflows, strengthening cross-category communication, and investing in permanent education to enhance care and reduce underreporting in highly complex health services.